Pandemic synergies: a possibility for the rural world? (Revista LIDER, 2021)
Countries such as Spain, where the demographic reality has been demanding answers tonew needs for decades, are facing numerous questions about the future. Their territories and their urban and rural populations have been drifting apart in these new and imposing realities. The rural territory has been forgotten in an increasingly faster and more technified framework. The COVID-19 pandemic has bypassed all containment measures and any foreseen analysis has paralyzed the world as we knew it. However, in this stark reality, new challenges or new challenges appear in which the rural world can step out of its secondary role and approach new possibilities. Possibilities that many of the citizens have begun to demand after living a confinement never imagined. Through demographic data of the province of Albacete, it is visualized and counted if this new reality is reflected in an increase of the inhabitants in rural areas and, although the actuality of the subject still does not allow an extensive development on it, the advance in this province is described, as an example of what could increase in the near future answering the question: is the pandemic a new sign or a possibility for the return to the ruralization?